PREDICTORS OF LATE INITIATION OF ANTENATAL CARE AMONG MUSLIM WOMEN IN PIDIE DISTRICT, ACEH - Mira Fajarina; Reka Julia Utama; Gadis Halizasia; Fitria Fitria (Universitas Bina Bangsa Getsempena, 2024)
Late initiation of antenatal care (ANC) remains a public health concern in Aceh, contributing to adverse maternal and neonatal outcomes. This study aimed to identify predictors of late ANC initiation and factors influencing ANC visit frequency among Muslim women in Pidie District. A predictive correlational study was conducted with 80 postpartum women selected using purposive sampling. Data were collected through structured questionnaires covering sociodemographic characteristics, obstetric history, knowledge, perceptions, beliefs, and social support. Analyses included descriptive statistics, Chi-square tests, Spearman correlation, and binary logistic regression. Results showed that 55% of participants initiated ANC after 12 weeks of gestation, with only 25% completing the recommended minimum of four visits. Key barriers included long distances to health facilities (62%), cultural or religious beliefs (35%), economic constraints (28%), and limited ANC knowledge (40%). Logistic regression identified significant predictors of late ANC initiation: distance from health facility (AOR = 1.08; p = 0.005), lower knowledge about ANC (AOR = 0.72; p = 0.03), and history of abortion (AOR = 6.12; p = 0.01). Family support, particularly from husbands, and guidance from community health volunteers were also influential in timely ANC attendance. In conclusion, both accessibility and maternal knowledge are key determinants of ANC utilization in Pidie. Interventions such as community-based education, telehealth support, and culturally sensitive counseling are recommended to improve timely ANC initiation and adherence, ultimately enhancing maternal and neonatal health outcomes.